LAS «REFORMAS» DE URUKAGINA - Molina, Manuel (Antigüedad y Cristianismo, 1995)
In this article a study is made of the Sumerian text known as The "Refomzs" of UruKAgina, taking into consideration aspects such as the composition of the text, problems related to its translation, the contents and the real significance of "The Reforms", and the social, economical,political and ideological context in which it was promulgated. Also a transliteration and translation of The "Refomzs". . . (UKg 4-5 = cones B-Care provided. (...)